2019
DOI: 10.1161/hypertensionaha.118.12012
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Actions of an Innovative Bispecific Designer Peptide

Abstract: Despite optimal current therapies, cardiovascular disease (CVD) remains the leading cause for death worldwide. Importantly, advances in peptide engineering have accelerated the development of innovative therapeutics for diverse human disease states. Additionally, the advancement of bispecific therapeutics targeting more than one signaling pathway represents a highly innovative strategy for the treatment of CVD. We therefore engineered a novel designer peptide which simultaneously targets the particulate guanyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…A first-in-class bispecific designer peptide that cotargets Mas and pGC-A in one peptide entity was recently engineered (Meems et al, 2019). This designer peptide NPA7 replaces the 9-amino-acid N terminus of BNP1-32 with the Mas agonist Ang 1 - 7 (Fig.…”
Section: Dual Receptor Activation Of Particulate Guanylyl Cyclase mentioning
confidence: 99%
See 1 more Smart Citation
“…A first-in-class bispecific designer peptide that cotargets Mas and pGC-A in one peptide entity was recently engineered (Meems et al, 2019). This designer peptide NPA7 replaces the 9-amino-acid N terminus of BNP1-32 with the Mas agonist Ang 1 - 7 (Fig.…”
Section: Dual Receptor Activation Of Particulate Guanylyl Cyclase mentioning
confidence: 99%
“…In a recent report, pGC-A and Mas activation by NPA7 was validated and it was shown that NPA7 is biologically active in vivo with potent and more sustained cardiorenal actions that go beyond Mas or pGC-A alone (Meems et al, 2019). Further validation of stimulation of both receptors in vitro was shown and increases in the second messengers of pGC-A and Mas in HEK293 cells with increases in cGMP and cAMP, respectively, were demonstrated.…”
Section: Dual Receptor Activation Of Particulate Guanylyl Cyclase mentioning
confidence: 99%
“…The addition of neprilysin inhibition provides modulatory effect on endogenous vasoactive peptides such as natriuretic peptides and bradykinin, resulting in beneficial remodelling and vasodilation (D'Elia et al, 2017). Given the therapeutic success of sacubitril–valsartan via natriuretic peptide augmentation, designer natriuretic peptide analogues such as MANP (also known as ZD100) (McKie et al, 2014), CRRL‐269 (Chen, Harty, et al, 2019), NPA7 (Meems et al, 2019), C53 (Chen et al, 2019) or cenderitide (also known as CD‐NP) (Kawakami et al, 2018) may offer an alternative, yet complementary, therapeutic strategy for cardiorenal syndrome and are currently under advanced preclinical and clinical development. Empagliflozin and canagliflozin, sodium‐glucose cotransporter 2 (SGLT2) inhibitors, demonstrated beneficial cardiovascular and all‐cause mortality and hospitalization in diabetic patients with high cardiovascular risk (Zinman et al, 2015).…”
Section: Diagnosis Prognosis and Treatment Of Cardiorenal Syndromementioning
confidence: 99%
“…Since Ang-(1–7) possesses a short half-life in plasma, alternative Ang-(1–7) mimetics (cyclic Ang-(1–7), HPβCD-Ang-(1–7), NPA7, TXA127) and MasR agonists (AVE 0991, CGEN-856, CGEN-857) have been successfully tested in experimental models against oxidation, thrombogenesis, fibrosis, inflammation, endothelial function, and high blood pressure [ 71 , 126 ] ( Figure 3 ). In humans, HPβCD-Ang-(1–7) (hydroxypropyl β-cyclodextrin-Ang-(1–7)) also improved the recovery from a supramaximal physical exercise [ 127 ], and NPA7 (a fusion peptide of BNP (B-type natriuretic peptide) and Ang-(1–7)) reduced blood pressure and cardiac uploading [ 128 ]. In turn, TXA127 has been catalogued as an orphan drug by the Food and Drug Administration (FDA) for the treatment of pulmonary arterial hypertension, while is being tested in the TXA COVID-19 Clinical Trial to prevent multi-organ failure in patients with moderate to severe COVID-19 [ 129 ].…”
Section: Introductionmentioning
confidence: 99%